Family Support and Its Impact on the Motivation of Schizophrenia Clients - Patricia, Helena; Irman, Veolina; Apriyeni, Emira; Rahayuningrum, Dwi Christina (PT. Riset Press International, 2025)
Family support plays a significant role in influencing the recovery motivation of schizophrenia clients in West Sumatra, which ranks as the fourth province with the highest prevalence of mental disorders in Indonesia, with 10,816 individuals affected. This study aims to examine the relationship between family support and the motivation of schizophrenia clients at the Yayasan Pelita Jiwa Insani. This quantitative research, with a cross-sectional approach, was conducted from March to April 2024. The population consisted of 102 schizophrenia clients, with a purposive sample size of 81 respondents. Data collection used questionnaires and interviews, and analysis was conducted using univariate and bivariate methods with the chi-square test. Results showed that 56.8% of clients had low family support and low motivation. A significant relationship was found between family support and motivation (p = 0.048). These findings are expected to help enhance the motivation of clients undergoing rehabilitation at the foundation and contribute to nursing knowledge as a reference for further research.